Sex segregation in the workplace : trends, explanations, remedies - Reskin, Barbara F.; National Research Council (U.S.). Committee on Women's Employment and Related Social Issues (Washington, D.C. : National Academy Press, 1984)
How pervasive is sex segregation in the workplace? Does the concentration of women into a few professions reflect their personal preferences, the "tastes" of employers, or sex-role socialization? Will greater enforcement of federal antidiscrimination laws reduce segregation? What are the prospects for the decade ahead? These are among the important policy and research questions raised in this comprehensive volume, of interest to policymakers, researchers, personnel directors, union leaders--anyone concerned about the economic parity of women
Extent, trends, and projections for the future -- Trends in occupational segregation by sex and race, 1960-1981 / Andrea H. Beller -- A woman's place is with other women: sex segregation within organizations / William T. Bielby, James N. Baron -- Job changing and occupational sex segregation: sex and race comparisons / Rachel A. Rosenfeld -- Commentary / Pamela Stone Cain -- Occupational sex segregation: prospects for the 1980s / Andrea H. Beller, Kee-ok Kim Han -- Explaining segregation: theoretical perspectives and empirical evidence -- Occupational segregation and labor market discrimination / Francine D. Blau -- Toward a general theory of occupational sex segregation: the case of public school teaching / Myra H. Strober -- Commentary: Strober's theory of occupational sex segregation / Karen Oppenheim Mason -- Work experience, job segregation, and wages / Mary Corcoran, Greg J. Duncan, Michael Ponza -- Sex typing in occupational socialization / Margaret Mooney Marini, Mary C. Brinton -- Commentary / Wendy C. Wolf -- Institutional factors contributing to sex segregation in the workplace / Patricia A. Roos, Barbara F. Reskin -- Commentary: The need to study the transformation of job structures / Maryellen R. Kelley -- Reducing segregation: the effectiveness of interventions -- Job integration strategies: today's programs and tomorrow's needs / Brigid O'Farrell, Sharon L. Harlan -- Occupational desegregation in CETA programs / Linda J. Waite, Sue E. Berryman -- Commentary / Wendy C. Wolf -- Concluding remarks / Francine D. Blau.
Revised versions of papers originally presented at a workshop held in May, 1982.
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Sex discrimination in employment -- United States -- Congresses; Sex discrimination against women -- United States -- Congresses; Sex discrimination in employment -- United States -- Congresses; Sex discrimination against women -- United States -- Congresses; Discrimination sexuelle dans l'emploi -- États-Unis -- Congrès.; Discrimination à l'égard des femmes -- États-Unis -- Congrès.; Discrimination sexuelle dans l'emploi -- États-Unis -- Congrès.; Discrimination à l'égard des femmes -- États-Unis -- Congrès.; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Sex discrimination against women; Sex discrimination in employment; United States; USA; Arbeitsplatz; Aufsatzsammlung; Geschlechterrolle; Rassenfrage; Vrouwenarbeid; Vrouwendiscriminatie; Sex discrimination in employment -- United States -- Congresses; Sex discrimination against women -- United States -- Congresses; proceedings (reports); Conference papers and proceedings; Congressen (vorm); Conference papers and proceedings; Actes de congrès.